45. CURRENT STATUS FOR HOME-BASED MEDICAL TESTING SERVICES IN BAC TU LIEM DISTRICT, HANOI, 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status and demand for home-based medical testing services among residents in selected wards of Bac Tu Liem District, Hanoi during 2023–2024.Subjects and Methods: A cross-sectional descriptive study was conducted. A total of 426 residents from three wards (Duc Thang, Dong Ngac, and Co Nhue 2) in Bac Tu Liem District were interviewed between 2023 and 2024.Results: Participants aged 18–45 years accounted for 57%, while those aged 46 and above made up 43%. The majority of respondents were female (71.6%), with 38.7% having completed upper secondary education. Most participants were freelance workers (51.4%), with a monthly income ranging from 5 to 10 million VND. Additionally, 71.6% reported having good health status. Of the respondents, 63.8% had never used home-based medical testing services. Among those aware of the service, 33.8% learned about it through friends or relatives. The majority of participants expressed willingness to pay for home-based medical testing packages within the range of 500,000 to 1,000,000 VND (39.7%).Conclusion: Our study, based on interviews with 426 residents, showed that the majority were aged 18–45, primarily freelance workers with good health status. A significant proportion had not previously used home-based medical testing services (63.8%), yet expressed a willingness to pay within the range of 500,000 - 1,000,000 VND.